Challenges to US hegemony : The case of Lula's Brazil - Vasileiou, Florentia (2023)
After his victory, Lula has been forthright about his vision of a Brazil that actively engages in foreign policy endeavours to restore its global position as a voice of the Global South independent of outside influence, particularly the US. This dissertation aims to determine whether Lula's Brazil could challenge US hegemony, specifically focusing on three separate domains: political, trade and dollar hegemony. Brazil has the ambition and ability to challenge the United States' dollar and trade hegemony through the promotion of both BRICS and regional currencies, as well as changes in trade operations aimed at opposing the dollar. Nonetheless, it is unclear whether Brazil can truly challenge US political hegemony in the near future, despite evidence that Brazil intends to strengthen its political dominance through BRICS and regional institutions.